Fluorescence or X‐ray cholangiography in elective laparoscopic cholecystectomy: a randomized clinical trial. Issue 6 (14th February 2020) - Lehrskov, L. L.; Westen, M.; Larsen, S. S.; Jensen, A. B.; Kristensen, B. B.; Bisgaard, T.
Abstract : Background: Safe laparoscopic cholecystectomy may necessitate biliary imaging, and non‐invasive fluorescence cholangiography may have advantages over contrast X‐ray cholangiography. This trial compared fluorescence and X‐ray cholangiography for visualization of the critical junction between the cystic, common hepatic and common bile ducts. Methods: This non‐inferiority blinded RCT included patients who had either intraoperative fluorescence cholangiography using 0·05 mg/kg indocyanine green or X‐ray cholangiography during elective laparoscopic cholecystectomy. Results: Between March 2015 and August 2018, a total of 120 patients were randomized (60 in each group). There were no drop‐outs and 30‐day follow‐up data were available for all patients. In intention‐to‐treat analysis, there was no difference between the fluorescence and X‐ray cholangiography groups in ability to visualize the critical junction (49 of 60 versus 51 of 60 respectively; P  = 0·230). Fluorescence cholangiography was faster by a few minutes: median 2·0 (range 0·5–5·0) versus 4·8 (1·3–17·6) min ( P  < 0·001). Conclusion: Fluorescence cholangiography was confirmed to be non‐inferior to X‐ray cholangiography in visualizing the critical junction during laparoscopic cholecystectomy. Registration number: NCT02344654 ( http://www.clinicaltrials.gov ). Abstract : A total of 120 patients were randomized to either intraoperative fluorescence or X‐ray cholangiography during planned laparoscopic cholecystectomy. There was no difference between groups in the rate of visualization of the critical junction between the cystic duct, common hepatic duct and common bile duct. Fluorescence cholangiography may be a valid alternative to X‐ray cholangiography for visualization of the critical junction. The future? Abstract : Antecedentes: La práctica de una colecistectomía laparoscópica segura puede requerir imágenes de la vía biliar, en las cuales la colangiografía con fluorescencia no invasiva puede tener ventajas sobre la colangiografía con contraste con rayos X. Este ensayo comparó la colangiografía con fluorescencia con la colangiografía con rayos X para la visualización de la unión crítica entre el conducto cístico, el conducto hepático común y los conductos biliares comunes. Métodos: Ensayo clínico aleatorizado, ciego, de no inferioridad que incluyó a 120 pacientes en los que durante la colecistectomía laparoscópica electiva se practicó una colangiografía con fluorescencia intraoperatoria utilizando 0, 05 mg/kg de verde de indocianina o una colangiografía con rayos X. Resultados: De marzo de 2015 a agosto de 2018, se aleatorizaron un total de 120 pacientes (6 en cada grupo), en los que no hubo abandonos y con datos de seguimiento de 30 días disponibles en todos ellos. Basado en un análisis por intención de tratamiento, la capacidad de visualizar la unión crítica fue igual entre los dos grupos (49/60 versus 51/60, P = 0, 23). La colangiografía con fluorescencia fue más rápida de realizar, en unos pocos minutos (mediana 2 min (rango 0, 5‐5, 0) versus 5 min (rango 5, 2‐17, 6), P < 0, 001). Conclusión: Se confirmó que la colangiografía con fluorescencia no fue inferior a la colangiografía con rayos X para visualizar la unión crítica durante la colecistectomía laparoscópica.